2007
DOI: 10.1007/s11096-007-9168-1
|View full text |Cite
|
Sign up to set email alerts
|

Medicine-taking behaviour and drug-related problems in adolescents of a Swedish high school

Abstract: There is a need to develop the interface between pharmacy practitioners and adolescents, as the study has demonstrated frequent use of OTCs and prescription drugs as well as a high prevalence of DRPs in adolescents. The reasons for therapy failure, which was the most common problem, should be further explored and measures taken by pharmacists and physicians to minimise it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Given the different methodologies, we are unable to ascertain whether the prevalence of a frequent use of OTC medicines is lower or higher among the study population compared to their counterparts in other countries. It appears, however, to be of the same magnitude as shown in other western European studies, where 43.3% of adolescents used OTC medicines at least once per month [22].…”
Section: Discussionsupporting
confidence: 71%
“…Given the different methodologies, we are unable to ascertain whether the prevalence of a frequent use of OTC medicines is lower or higher among the study population compared to their counterparts in other countries. It appears, however, to be of the same magnitude as shown in other western European studies, where 43.3% of adolescents used OTC medicines at least once per month [22].…”
Section: Discussionsupporting
confidence: 71%
“…[6] Many studies in different countries also showed that the prevalence of self-medication in children and adolescent was high. [7891011121314151617] Although health services are free in Kuwait, the high prevalence of self-medication could be due to the high living standard and the availability of large varieties of drugs in the market. In the present study, self-medication decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often make their decisions about what OTC drugs to use and when to use them on the basis of previous use and familiarity with a specific brand. 5 Studies have shown that teenagers especially are greatly influenced by parents and peers [6][7][8] and easily adapt the drugtaking behaviour of others. 7,8 According to Swedish therapy guidelines, paracetamol is the firstline treatment of mild or moderate pain and is considered harmless if taken as directed (≤4 g/d for adults).…”
Section: Introductionmentioning
confidence: 99%